Chemical communication in scarab beetles: reciprocal behavioral agonist-antagonist activities of chiral pheromones. - Leal, W S (1996)
A novel mechanism of reciprocal behavioral agonist-antagonist activities of enantiomeric pheromones plays a pivotal role in overcoming the signal-to-noise problem derived from the use of a single-constituent pheromone system in scarab beetles. Female Anomala osakana produce (S, Z)-5-(+)-(1-decenyl)oxacyclopentan-2-one, which is highly attractive to males; the response is completely inhibited even by 5% of its antipode. These two enantiomers have reverse roles in the Popillia japonica sex pheromone system. Chiral GC-electroantennographic detector experiments suggest that A. osakana and P. japonica have both R and S receptors that are responsible for behavioral agonist and antagonist responses.